Energetic vs structural study of two biomass degradation derivatives: 2-Cyclopentenone and 3-methyl-2-cyclopentenone. (May 2019) - Silva, Ana L.R.; Moura, Cosme; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Combustion enthalpies of 2-cyclopentenone and 3-methyl-2-cyclopentenone have been determined by combustion calorimetry. Enthalpies of vaporization of two cyclopentenone derivatives have been measured by Calvet Microcalorimetry. Gas-phase enthalpies of formation for two cyclopentenones were estimated from computational approach. Hydrogenation enthalpies of 2-cyclopentenone and 3-methyl-2-cyclopentenone were calculated. Abstract: The standard molar enthalpies of formation in the gaseous state, at T  = 298.15 K, of the 2-cyclopentenone and 3-methyl-2-cyclopentenone were derived from their standard molar energies of combustion and from their standard molar enthalpies of vaporization, obtained from static-bomb combustion calorimetry measurements and high-temperature Calvet microcalorimetry, respectively. The enthalpies of hydrogenation of the two cyclopentenones were derived from their gas-phase enthalpies of formation and the gas-phase enthalpies of formation of the corresponding cycloalkanones. The gas-phase standard molar enthalpy of formation of the compounds studied were also obtained using high level ab initio calculations and are in very good agreement with the experimental ones. In addition, thermochemical parameters associated to 2-cyclopentenone and 3-methyl-2-cyclopentenone transformations were investigated using the G3(MP2)//B3LYP level of theory. The conversions of both compounds to longer chain alkanes were found to be thermodynamically favourable.